The website-based eaTracker® 'My Goals' feature: a qualitative evaluation. Issue 5 (19th December 2016) - Lieffers, Jessica RL; Haresign, Helen; Mehling, Christine; Arocha, Jose F; Hanning, Rhona M
Abstract: Objective: In 2011, Dietitians of Canada added 'My Goals' to its website-based nutrition/activity tracking program (eaTracker ®, http://www.eaTracker.ca/ ); this feature allows users to choose 'ready-made' or 'write-your-own' goals and to self-report progress. The purpose of the present study was to document experiences and perceptions of goal setting and My Goals, and report users' feedback on what is needed in future website-based goal setting/tracking tools. Design: One-on-one semi-structured interviews were conducted with (i) My Goals users and (ii) dietitians providing a public information support service, EatRight Ontario (ERO). Setting: My Goals users from Ontario and Alberta, Canada were recruited via an eaTracker website pop-up box; ERO dietitians working in Ontario, Canada were recruited via ERO. Subjects: My Goals users ( n 23; age 19–70 years; 91 % female; n 5 from Alberta/ n 18 from Ontario) and ERO dietitians ( n 5). Results: Dietitians and users felt goal setting for nutrition (and activity) behaviour change was both a beneficial and a challenging process. Dietitians were concerned about users setting poor-quality goals and users felt it was difficult to stick to their goals. Both users and dietitians were enthusiastic about the My Goals concept, but felt the current feature had limitations that affected use. Dietitians and users provided suggestions to improve My Goals (e.g. more prominent presence of My Goals in eaTracker; assistance with goal setting; automated personalized feedback). Conclusions: Dietitians and users shared similar perspectives on the My Goals feature and both felt goal use was challenging. Several suggestions were provided to enhance My Goals that are relevant to website-based goal setting/tracking tool design in general.